1981
DOI: 10.1002/ana.410090116
|View full text |Cite
|
Sign up to set email alerts
|

Postictal pleocytosis

Abstract: Six patients showed a transient and otherwise unexplained cerebrospinal fluid (CSF) pleocytosis following a flurry of generalized convulsions. Each had an obvious cause for repeated seizures. No evidence was found for an infectious, inflammatory, neoplastic, or other cause for the pleocytosis. All CSF specimens were clear and colorless, under normal pressure, and bacteriologically sterile. The maximal leukocyte count ranged from 9 to 80 per cubic millimeter and reached a maximum on the day after cessation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1
2

Year Published

1983
1983
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 5 publications
1
28
1
2
Order By: Relevance
“…It had also been reported that patients who are first seen with seizures have a CSF pleocytosis as the result of the seizure itself 24 . Besides that, patients with seizures do form a large proportion of those The CSF profile, like any other laboratory determination, should be evaluated within the clinical context of the individual case.…”
Section: Discussionmentioning
confidence: 97%
“…It had also been reported that patients who are first seen with seizures have a CSF pleocytosis as the result of the seizure itself 24 . Besides that, patients with seizures do form a large proportion of those The CSF profile, like any other laboratory determination, should be evaluated within the clinical context of the individual case.…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies have reported postictal CSF pleocytosis in patients with epilepsy following an episode of status epilepticus (Aminoff and Simon, 1980;Woody et al, 1988;Barry and Hauser, 1994;Rider et al, 1995) or prolonged seizure (Schmidley and Simon, 1981;Edwards et al, 1983;Prokesch et al, 1983;Devinsky et al, 1988;Rider et al, 1995). However, in most of these studies, observed changes were minimal.…”
Section: Can Csf Abnormalities Be Caused By Convulsions?mentioning
confidence: 90%
“…Whether convulsions cause changes in the CSF is frequently debated as there is inconsistent information about this in the literature (Aminoff and Simon, 1980;Schmidley and Simon, 1981;Edwards et al, 1983;Simon, 1985;Thompson and Salinsky, 1988;Woody et al, 1988). The reported frequency of seizure-induced CSF abnormalities has been estimated to be as high as 30% (Prokesch et al, 1983).…”
Section: Can Csf Abnormalities Be Caused By Convulsions?mentioning
confidence: 94%
“…Em medicina humana, as convulsões têm sido associadas a alterações como pleocitose e aumento dos níveis de proteínas (AMINOFFE; SIMON, 1980;SIMON, 1981;EDWARDS et al, 1983, PROKESCH et al, 1983, entretanto, a ocorrência dessas anormalidades na análise de LCR após um EC são muito variáveis, tendo sido observadas em aproximadamente 30% dos casos (EDWARDS et al, 1983;PROKESCH et al, 1983).…”
Section: Introductionunclassified
“…Os mecanismos pelos quais as convulsões podem influenciar a composição fisiológica do LCR não são claros, porém acredita-se que ocorra alteração na barreira hematencefálica e liberação de substâncias quimiotáticas para o LCR durante as crises epilépticas (SCHMIDLEY; SIMON, 1981;EDWARDS et al, 1983).…”
Section: Introductionunclassified